A Lack of Association Between Blood Glutamate and Anxiety Levels in Pre- delivery Pregnant Women - Tsesis, Svetlana; Silberstein, Tali; Zlotnik, Alexander; Boyko, Matthew; Kuts, Ruslan; N. Azab, Abed (Current Pharmaceutical Analysis, 2016)
Background: Pregnant women who are planned to undergo a cesarean section (CS) may suffer high levels of anxiety. Because glutamate is an excitatory neurotransmitter that is associated with stress conditions and anxiety, it is possible that anxious pregnant women may have altered blood glutamate levels which may influence the wellbeing of the mother and fetus. Objectives: This study was undertaken to examine anxiety levels in pregnant women planned for vaginal delivery (VD) as compared to women scheduled for elective CS, and, to determine the association between severity of anxiety and blood glutamate levels in pre-delivery women. Subjects and Methods: Anxiety was assessed in 3rd trimester, pre-delivery pregnant women (≥18 years old) who met the inclusion criteria of the study and signed a written informed consent to participate. The study was approved by the local Ethical Committee. Anxiety was assessed in 100 women who were scheduled for a spontaneous VD and 100 women who were scheduled for an elective CS using the Hamilton Anxiety Rating Scale (HARS). After completing the HARS, a blood sample was collected for determination of glutamate levels. Mann-Whitney’s test was used to evaluate differences in anxiety levels between the groups. The association between glutamate levels and severity of anxiety was examined using Spearman’s correlation test. Results: Women who underwent VD had a significantly higher level of anxiety as compared to women who underwent a CS (HARS score 12.5 ± 0.73 vs. 6.6 ± 0.7, P < 0.001, respectively). Blood glutamate levels did not differ significantly between the groups (71.9 ± 2.8 vs. 77.8 ± 3.1 μM/L, P = 0.15, respectively). Moreover, there was no association between level of anxiety and glutamate levels in both groups (VD group: R = - 0.084, P = 0.42; CS group: R = 0.124, P = 0.24). Conclusion: The mechanism of pre-delivery anxiety seems to be glutamate-independent. The finding that women who underwent a VD had high levels of anxiety underscores the need for better pre-partum educational programs aimed to reduce anxiety in pregnant women scheduled for a VD.
Keywords: Anxiety